EFFECTIVENESS OF INTRA ORAL SCANNING FOR COMPLETE DENTURES - Asha S Hariharan, Revathi Duraisamy, Dhanraj Ganapathy (Drugs and Cell Therapies in Hematology, 2021)
INTRODUCTION: With the advancements in the technology, CAD CAM has opened avenues to a partial or complete workflow for the fabrication of complete dentures.CAD CAM workflow comes with the advantage of , reduction in time of both clinical and laboratory procedures, higher patient satisfaction, better clinician acceptance, and reduced procedure time. AIM: To assess the effectiveness of intraoral scanning technique for completely edentulous arches through in vitro measurements and patient perception . MATERIALS AND METHODS: 7 edentulous patients were included, for whom two sets of impressions were made. Group 1: Conventional Impression followed by die stone model Group 2: Digital Impression using intra oral scanner followed by resin printed model ( Trios, 3shape ). The discrepancies in the models were measured using a digital vernier calliper by measuring the distance between the tuberosities and between the 1st and second palatal rugae. Denture bases were fabricated on both the models and patient perception of retention was evaluated using VAS scale during speech and swallowing. Independent T-test was performed to analyse the differences in the casts. Mann-Whitney U test was performed for patient related outcome measures. RESULTS: Based on the measurements on the cast showed that there was a statistically significant difference between the two impressions technique, The conventional impression technique being superior, but this difference was within clinically acceptable range(0.2428±0.7868- in palatal rugae region). Based on the patient based outcomes, the conventional impression group fared better(8.14±0.378). Swallowing was most affected in the digital impression group. CONCLUSION: Conventional impression technique may be the gold standard for complete denture impressions, but intra oral scanning is a promising alternative which could be the future of complete denture fabrication.